EFFECT OF STORAGE TEMPERATURE ON LOW-COLESTEROL MAYONNAISE BASED ON CANOLA OIL (CO) WITH VIRGIN COCONUT OIL (VCO) - Mutsyahidan, Arif Murtaqi Akhmad; Liputo, Siti Aisa; Une, Suryani; Isima, Rahman; Podungge, Fani Fadilah; Nurdin, Delia; Djama, Anisa; Nurdin, Alwina (Prosiding Seminar Nasional Mini Riset Mahasiswa, 2024)
Mayonnaise is an emulsion product that contains high fat. This study aims to determine the chemical and sensory properties and to determine the stability of mayonnaise emulsion made from canola oil with VCO at different temperatures. The design carried out in this study included a completely randomised design (CRD) with different storage temperature factors. Data were analysed by statistical test (ANOVA). Testing parameters include peroxide number, emulsion stability, organoleptic and blood cholesterol test. Based on the research obtained, the peroxide value at 150C storage temperature produces a peroxide value of 0.64 Meq / Kg, at 30oC storage temperature produces 1.19 Meq / Kg and at 45oC storage temperature produces 1.93 Meq / Kg. In the flavour organoleptic test with a storage temperature of 150C resulted in a value of 4.1 (Neutral), a storage temperature of 300C resulted in a value of 3.5 (Somewhat dislike), and a storage temperature of 450C resulted in a value of 3.4 (Somewhat dislike). In the mayonnaise emulsion stability test at 15°C showed stable results, no phase separation, at 30°C showed unstable results, there was phase separation and at 45°C showed unstable results, there was phase separation. The blood cholesterol level test resulted in an average value of 193.2 Mg/dl before consuming mayonnaise, after the panellists consumed 50 grams of mayonnaise the panellists experienced an increase in blood cholesterol levels with an average value of 200 Mg/dl, at 120 minutes the panellists experienced a decrease in cholesterol levels with an average value of 137.2 Mg/dl.